2015
DOI: 10.3389/fmicb.2015.00626
|View full text |Cite
|
Sign up to set email alerts
|

The molecular dimension of microbial species: 2. Synechococcus strains representative of putative ecotypes inhabiting different depths in the Mushroom Spring microbial mat exhibit different adaptive and acclimative responses to light

Abstract: Closely related strains of thermophilic Synechococcus were cultivated from the microbial mats found in the effluent channels of Mushroom Spring, Yellowstone National Park (YNP). These strains have identical or nearly identical 16S rRNA sequences but are representative of separate, predicted putative ecotype (PE) populations, which were identified by using the more highly resolving psaA locus and which predominate at different vertical positions within the 1-mm-thick upper-green layer of the mat. Pyrosequencing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 36 publications
3
45
0
Order By: Relevance
“…Soil and fresh-water cyanobacteria encounter FRL because it penetrates more deeply into soils and because plant canopies strongly enrich for FRL because of absorption by chlorophylls (Chl) a and b (Gan and Bryant, 2015). Similar effects occur in microbial mats and sometimes in blooms, where self-shading can provide a powerful selection for alternative, light-harvesting antenna systems (Kühl and Jørgensen, 1994; Nowack et al, 2015; Olsen et al, 2015). We recently discovered two photoacclimation processes that occur in some cyanobacteria in FRL and/or low light, here denoted Far-Red Light Photoacclimation (FaRLiP) (Gan et al, 2014, 2015; Gan and Bryant, 2015) and Low Light Photoacclimation (LoLiP) (Nowack et al, 2015; Olsen et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Soil and fresh-water cyanobacteria encounter FRL because it penetrates more deeply into soils and because plant canopies strongly enrich for FRL because of absorption by chlorophylls (Chl) a and b (Gan and Bryant, 2015). Similar effects occur in microbial mats and sometimes in blooms, where self-shading can provide a powerful selection for alternative, light-harvesting antenna systems (Kühl and Jørgensen, 1994; Nowack et al, 2015; Olsen et al, 2015). We recently discovered two photoacclimation processes that occur in some cyanobacteria in FRL and/or low light, here denoted Far-Red Light Photoacclimation (FaRLiP) (Gan et al, 2014, 2015; Gan and Bryant, 2015) and Low Light Photoacclimation (LoLiP) (Nowack et al, 2015; Olsen et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…Similar effects occur in microbial mats and sometimes in blooms, where self-shading can provide a powerful selection for alternative, light-harvesting antenna systems (Kühl and Jørgensen, 1994; Nowack et al, 2015; Olsen et al, 2015). We recently discovered two photoacclimation processes that occur in some cyanobacteria in FRL and/or low light, here denoted Far-Red Light Photoacclimation (FaRLiP) (Gan et al, 2014, 2015; Gan and Bryant, 2015) and Low Light Photoacclimation (LoLiP) (Nowack et al, 2015; Olsen et al, 2015). During the FaRLiP response, specialized paralogous proteins replace 17 core subunits of the three major photosynthetic complexes: Photosystem (PS) I, PS II, and the phycobilisome.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In particular, the speciation of Synechococcus has been extensively studied with respect to the physicochemical gradients (especially light and temperature) that occur in this system, and putative ecotypes have been identified that are differently distributed as a function of such gradients and that were predicted to have different adaptations to light (Becraft et al ., ; ). Isolates of high‐light‐adapted and low‐light‐adapted putative ecotypes were obtained, and these isolates were characterized with respect to their growth behavior under different irradiance conditions (Nowack et al ., ). These studies showed that low‐light‐adapted ecotypes grow faster at low irradiance but are more sensitive to high light, while high‐light‐adapted isolates tolerate high light much better but are unable to grow as rapidly as low‐light‐adapted isolates at low irradiance.…”
Section: A Simpler Alternative To Farlip: Low‐light Photoacclimation mentioning
confidence: 97%
“…These PEs were shown to inhabit different locations within the vertical profile of the mat, with PEs B 9, A1, A4, then A14 progressing from the surface to 1 mm below [2]. More recently, Synechococcus isolates that share the same psaA sequence as PEs A1 (strain JA-3-3Ab), A4 (strain 65AY6A5), and A14 (strain 60AY4M2) demonstrated different adaptive and acclimative responses to light intensity and quality, with optimal growth in vitro similar to conditions present where they can be found in the vertical profile of the mat in situ [30]. Comparative genomics and transcriptomics have elucidated genetic differences among these PEs that explain their different metabolic requirements (e.g., low-light adapted PEs were found to have an extra cassette of photosynthetic antenna genes that allow spectral fine tuning under low-light conditions) [34].…”
Section: Application Of Ecotype Simulation To Predict Species In Natumentioning
confidence: 95%